Comparison of the centering ability of Wave·One and Reciproc nickel-titanium instruments in simulated curved canals - Young-Jun Lim; Su-Jung Park; Hyeon-Cheol Kim; Kyung-San Mi (Korean Academy of Conservative Dentistry, 2013)
Objectives The aim of this study was to evaluate the shaping ability of newly marketed single-file instruments, Wave·One (Dentsply-Maillefer) and Reciproc (VDW GmbH), in terms of maintaining the original root canal configuration and curvature, with or without a glide-path. Materials and Methods According to the instruments used, the blocks were divided into 4 groups (n = 10): Group 1, no glide-path / Wave·One; Group 2, no glide-path / Reciproc; Group 3, #15 K-file / Wave·One; Group 4, #15 K-file / Reciproc. Pre- and post-instrumented images were scanned and the canal deviation was assessed. The cyclic fatigue stress was loaded to examine the cross-sectional shape of the fractured surface. The broken fragments were evaluated under the scanning electron microscope (SEM) for topographic features of the cross-section. Statistically analysis of the data was performed using one-way analysis of variance followed by Tukey's test (α = 0.05). Results The ability of instruments to remain centered in prepared canals at 1 and 2 mm levels was significantly lower in Group 1 (p < 0.05). The centering ratio at 3, 5, and 7 mm level were not significantly different. Conclusions The Wave·One file should be used following establishment of a glide-path larger than #15.